Immunotherapy in NSCLC patients with brain metastases. Understanding brain tumor microenvironment and dissecting outcomes from immune checkpoint blockade in the clinic. (September 2020) - Vilariño, N.; Bruna, J.; Bosch-Barrera, J.; Valiente, M.; Nadal, E.
Highlights: The brain microenvironment, including brain metastases (BM), is "immunologically cold". The mechanism of action of immunotherapy in the brain or BMs is not well understood. Intracranial responses can occur in patients with NSCLC receiving immunotherapy. Understanding the interplay of microenvironment and BMs may improve immunotherapy outcomes. Abstract: Background: Brain metastases are frequent complications in patients with non-small-cell lung cancer (NSCLC) associated with significant morbidity and poor prognosis. Our goal is to give a global overlook on clinical efficacy from immune checkpoint inhibitors in this setting and to review the role of biomarkers and molecular interactions in brain metastases from patients with NSCLC. Methods: We reviewed clinical trials reporting clinical outcomes of patients with NSCLC with brain metastases as well as publications assessing the tumor microenvironment and the complex molecular interactions of tumor cells with immune and resident cells in brain metastases from NSCLC biopsies or preclinical models. Results: Although limited data are available on immunotherapy in patients with brain metastases, immune checkpoint inhibitors alone or in combination with chemotherapy have shown promising intracranial efficacy and safety results. The underlying mechanism of action of immune checkpoint inhibitors in the brain niche and their influence on tumor microenvironment are still not known. Lower PD-L1 expression and less T CD8 + infiltration were found in brain metastases compared with matched NSCLC primary tumors, suggesting an immunosuppressive microenvironment in the brain. Reactive astrocytes and tumor associated macrophages are paramount in NSCLC brain metastases and play a role in promoting tumor progression and immune evasion. Conclusions: Discordances in the immune profile between primary tumours and brain metastases underscore differences in the tumour microenvironment and immune system interactions within the lung and brain niche. The characterization of immune phenotype of brain metastases and dissecting the interplay among immune cells and resident stromal cells along with cancer cells is crucial to unravel effective immunotherapeutic approaches in patients with NSCLC and brain metastases.